Kinetics and mechanism of redox-coupled, long-range proton transfer in an iron-sulfur protein. Investigation by fast-scan protein-film voltammetry - Hirst, J; Duff, J; Jameson, G; Kemper, M; Burgess, B; Armstrong, F (1998)
Fast-scan protein-film voltammetry has been used to study and deconvolute the kinetics of proton-coupled electron transfer to and from the [3Fe-4S] cluster in Azotobacter vinelandii Ferredoxin I (Au Fd I). This crystallographically defined 7Fe ferredoxin contains a [3Fe-4S] cluster which takes up a proton when in its reduced (0) state. Results conform to a model for stepwise electron and proton transfers. Electron transfer to the cluster drives its protonation, whereas the rate of reoxidation of[3Fe-4S]0-H+ is controlled by the rate of release of the proton. The cluster is buried and inaccessible to solvent water molecules; an aspartate (D15) is located on the protein surface but otherwise proton transfer occurs across an aprotic barrier. The D15N mutant, in which this aspartate is replaced by asparagine, has also been studied. Rate constants for proton transfer in each direction and the accompanying energetics (reduction potentials and interdependent pK values of the cluster and aspartate) have been determined simultaneously by modeling voltammetric peak positions (measured over a range of scan rate and pH) using numerical (digital) simulation. For comparison, rates of proton- gated oxidation were measured independently using stopped-flow spectrophotometry. Proton transfer between the cluster and bulk water occurs over 100 times faster in the native protein than in D15N, and the kinetics are described by a mechanism in which the proton is transferred using the aspartate carboxylate. Lack of an H/D isotope effect suggests that this group acts as a short-range courier. The system provides an intriguing functional model for redox-driven proton pumps, being both well-defined at the molecular level and amenable to detailed study by film voltammetry.